Study on Indoor Air Quality (IAQ) Level and Sick Building Syndrome (SBS) at Dato’ Muhamad Salleh Perang Office Building - Johari, Mohammad Hamirul Helmie; Abdul Rahman, Mohd Fahmi (Progress in Engineering Application and Technology, 2024)
This study focuses the significant impact of poor Indoor Air Quality (IAQ) on the health and productivity of office building occupants, particularly in relation to Sick Building Syndrome (SBS), emphasizing the need for comprehensive research, adherence to IAQ regulations, and a focus on multiple IAQ parameters to create healthier work environments. This study aimed to assess Indoor Air Quality (IAQ) in the Dato' Muhamad Salleh Perang Building, identifying Sick Building Syndrome (SBS) symptoms, measuring IAQ parameters, and proposing practical solutions for a healthier office environment. The study employs quantitative methods, including IAQ measurements and SBS questionnaires, to thoroughly assess Indoor Air Quality (IAQ) and determine the prevalence of Sick Building Syndrome (SBS) symptoms among occupants in the Dato' Muhamad Salleh Perang Office Building. The findings showed that temperatures and RH were generally within acceptable ranges, air velocity and gaseous pollutants remained within permissible limits in all offices with low frequency of SBS-related symptoms. These symptoms were categorized into General discomfort, Throat and Chest problems, Nose problems, Skin complications, and Eye-related concerns. However, SBS symptoms highlighted the need for continuous monitoring and improvement efforts. Overall, this study contributes to the understanding of IAQ and SBS issues, offering insights that can inform practices for creating comfortable, safe, and productive workspaces. Future research recommendations include exploring additional IAQ parameters, assessing climate change impacts, and incorporating advanced monitoring tools for more accurate results.